Dinamica relației dintre migrație și dezvoltare. Perspective asupra cazului Republicii Moldova - Cristina HARUȚA (Revista Transilvană de Ştiinţe Administrative, 2016)
International migration has been associated for decades either with development or with underdevelopment of the origin and destination countries. For those who highlight the positive link between migration and development the benefits of human mobility reside in the financial and social remittances of the migrants, the brain gain, the transfers of goods/ideas/capital, strengthened local economies in countries of origin and alleviated levels of poverty in migrant households etc. Nonetheless, the existing empirical studies have shown that the migration-development nexus is complex and by no means unidirectional, therefore any context in which a certain degree of modernization or development is claimed to occur due to migration, has to be analyzed thoroughly and approached skeptically. The focus of this article is the migratory process in Republic of Moldova. I attempt to deconstruct and to analyze a range of different stances and perspectives that apply to migration and development in Moldova, although some of them have not been entirely validated from an empirical standpoint.